Allergy patient-specific IgE antibody shows significantly stability during 3 months of storage at multiple temperatures from −80 to 25°C - Huang, Zhifeng; Zhu, Huiqing; Xiao, Lexin; Liu, Tingting; Gan, Hui; Lin, Runpei; Luo, Wenting; Sun, Baoqing (Frontiers in Allergy, 2023)
The detection of allergen-specific IgE antibodies is an important biomarker for the diagnosis and treatment monitoring of allergic diseases. And the pre-analytical phase is an important part of the overall quality of the laboratory. In this study, 44 patients with allergic diseases (including 23 patients with allergic rhinitis, 12 patients with allergic rhinitis and asthma, and 9 patients with allergic dermatitis) were included in the outpatient center of the Department of Allergy, the First Affiliated Hospital of Guangzhou Medical University. We mixed the serums of the above 44 patients (approximately 0.8 ml of serum volume per patient) into a large volume of serum pool (about 35 ml in total) and divided into 26 parts. And 26 serum samples were stored at 4 different temperatures for 90 days to observe the stability of sIgE antibodies to 16 allergens in serum. The results show that serum sIgE antibody titers in patients with allergic diseases show significant stability during 90 days of storage, even at room temperature. Good stability even after up to 10 freeze-thaw cycles under low temperature storage conditions.